Microcontroller based on catfish shredded spinner - Rahmad Surya Hadi Saputra; Lucky Andriansyah (Arwana: Jurnal Ilmiah Program Studi Perairan, 2025)
Indonesia's current cooking oil consumption reaches approximately 290 million tons per year. They are limiting the use of cooking oil to avoid hypercholesterolemia because it will result in excessive cholesterol, which will cause diseases such as heart disease, high blood pressure and others. Existing draining machines (spinners) are still used in the food industry. There are still some shortcomings because the need for an oil spinner used in the food industry differs for household kitchens. The existing conditions are like that, the existing oil spinners are still far from perfect. This study aims to produce good-quality shredded catfish and to streamline time using a microcontroller-based draining machine. The results of this study indicate that, based on 3 (three) draining treatments with different times, results in sample A 5 minutes (38.17%), sample B 10 minutes (26.51%), and sample C 15 minutes (18.20%). Thus, the fat content of shredded catfish with 15 minutes treatment (18.20%) has met the requirements set by the National Standardization Agency (BSN) for shredded processed products.